Circadian modulation of motivation in mice - Acosta, Julieta (2020)
Most living organisms have a circadian timing system adapted to optimize the daily rhythm of exposure to the environment. This circadian system modulates several behavioral and physiological processes, including the response to natural and drug rewards. Food is the most potent natural reward across species. Food-seeking is known to be mediated by dopaminergic and serotonergic transmission in cortico-limbic pathways. In the present work, we show evidence of a circadian modulation of motivation for food reward in young (4-months old) and aged (over 1.5 years old) C57BL/6 mice. Motivation was assayed through the progressive ratio (PR) schedule. Mice under a 12:12 light/dark (LD) cycle exhibited a diurnal rhythm in motivation, becoming more motivated during the night, coincident with their active phase. This rhythm was also evident under constant dark conditions, indicating the endogenous nature of this modulation. However, circadian arrhythmicity induced by chronic exposure to constant light conditions impaired the performance in the task causing low motivation levels. Furthermore, the day/night difference in motivation was also evident even without caloric restriction when using a palatable reward. All these results were found to be unaffected by aging. Taken together, our results indicate that motivation for food reward is regulated in a circadian manner, independent of the nutritional status and the nature of the reward, and that this rhythmic modulation is not affected by aging. These results may contribute to improve treatment related to psychiatric disorders or drugs of abuse, taking into account potential mechanisms of circadian modulation of motivational states.